Characterization of aerosol chemical properties from near-source biomass burning in the northern Indochina during 7-SEAS/Dongsha experiment - Chuang M.-T. (2014)
Biomass burning (BB) in Indochina produces a great amount of aerosols, but related information on this phenomenon is scarce. In the present study, aerosol samples were collected from Suthep Mountain (98° 53'E, 18° 48'N, 1396m) in Chiangmai, Northern Indochina, in March and April 2010. To our knowledge, this study is the first to reveal the chemical characteristics of BB aerosol near the burning sources in Indochina. The composition analyzed included water-soluble ions, carbonaceous fractions obtained using the thermal optical reflectance method, low-molecular-weight dicarboxylates, anhydrosugars, and water-soluble organic carbon (WSOC). Enriched tracers from the collected aerosols, such as potassium ion (K+) and levoglucosan, confirmed that the samples were influenced by BB activity. The percentage of K+ in PM2.5 (2.51%±0.31%) in the present study is higher than that in other studies. The analysis also showed that directly emitted organic carbon (OC) is the most abundant component in the collected particles. The percentage of WSOC in OC in the present study is greater than that in laboratory experiments. Moreover, the char-EC to soot-EC ratio (defined as the ratio of the subtraction of pyrolized OC from the measured EC1, EC1-OP, over the sum of EC2 and EC3) of 9.4±3.8 in PM2.5 is similar to the value of BB in the literature. Using the recognized BB aerosol tracers K+ and levoglucosan, the present study inferred that PM2.5 EC1-OP and OC3 are also good BB tracers near sources. The collected BB aerosols may have been contributed by the smoldering state of softwood burning. © 2012 Elsevier Ltd.